المشكل المعنوي واللغوي في القرآن الكريم عند النحاس دراسة لنماذج مختارة: Linguistic and Meaning Inexplicability in Quran According to Annahhas: An Analytical Study of Some Selected Examples - Nuhu, Ammar Abdussalam; Nashwan, Abdo Khaled (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تكوّن هذا البحث من مقدمة وتمهيد وثلاث مطالب ثم الخاتمة والمصادر. وذكر في المقدمة أهمية الموضوع وأسباب اختياره والدراسات السابقة ومنهج البحث ثم الخطة، وفي التمهيد: تعريف المشكل وأهمية دراسة علم المشكل القرآني، وتمّ تقسيم البحث إلى ثلاث مطالب: المطلب الأول: التعريف الموجز بأبي جعفر النحاس. المطلب الثاني: نماذج من مشكل المعنوي عند النحاس. المطلب الثالث: نماذج من مشكل اللغوي عند النحاس. وختم البحث بذكر الخاتمة والنتائج والمصادر والمراجع. وتوصّل البحث إلى نتائج منها: أنّ النحاس له اهتمام بالمشكل، حيث وقف البحث على ما يقارب أربعين موضعا في كتاب إعراب القرآن، وأنّ النحاس يستشكل ليجيب عنه لا للطعن في القرآن، وأنّ مشكل القرآن نسبي إلى الشخص، فما يكون مشكل عندك، فلا يلزم أن يكون مشكلا عند غيرك، وأنّ دراسة منهج المفسّر خلال المشكل مهم جدا، يقوي ملكة الدفاع عن القرآن. ABSTRACT This research is constituted of introduction, preamble, three chapters and conclusion. The research explaines in the introduction: the importance of the study, the causes of choosing it, literature review and the research proposal. While it is mentioned in the preamble; the definition of inexplicability, the importance of studying the inexplicability of the Quran and finally the research is categorized into three chapters: Chapter One: A Brief Biography of Abu Jafar Annahhas, chapter two: Samples of Semantic Inexplicability according to Annahhas and Chapter Three explaines: Samples of Lexical Inexplicability According to Annahhas. The research concludes with the mention of the findings of its and references. The researcher finds that Annahas has so much concern for the inexplicability of the Quran. This is obvious as the research was able to trace about forty places where Annahhas indicated to be inexplicable in the Quran in his book Iirabul Quran. He did this in order to give answers and meaningful explanations to them not to criticize the Quran. And that the inexplicability of the Quran is relative to individuals. Because what may be inexplicable to someone might not be to another. And also, the study of the inexplicability of Quran gives one the ability to defend the Quran.